2023
DOI: 10.3390/ijms24054763
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Exercise in Opioid Substitution Therapy: Mechanisms of Sequential Effects

Abstract: It is generally accepted that chronic opioid use is associated with structural and functional changes in the human brain that lead to an enhancement of impulsive behavior for immediate satisfaction. Interestingly, in recent years, physical exercise interventions have been used as an adjunctive treatment for patients with opioid use disorders (OUDs). Indeed, exercise has positive effects on both the biological and psychosocial basis of addiction, modifying neural circuits such as the reward, inhibition, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 240 publications
2
3
0
Order By: Relevance
“…The literature shows that access to a preoperatively planned exercise regimen may reduce prolonged opioid use. 40,41,42 Our findings complemented the literature, showing that patients more involved in very active activities (e.g., bicycling) before the surgery were more likely to be on high dose opioid use 6-12 months after surgery, while patients doing more lightly active activities (e.g., walking) before surgery were less likely to be on chronic opioid use 6-12 months after surgery (Figure 6). The type of surgery was also associated with higher chronic opioids (Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…The literature shows that access to a preoperatively planned exercise regimen may reduce prolonged opioid use. 40,41,42 Our findings complemented the literature, showing that patients more involved in very active activities (e.g., bicycling) before the surgery were more likely to be on high dose opioid use 6-12 months after surgery, while patients doing more lightly active activities (e.g., walking) before surgery were less likely to be on chronic opioid use 6-12 months after surgery (Figure 6). The type of surgery was also associated with higher chronic opioids (Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, in the exercise groups, there was a gradual decrease in the consumption of alcohol, benzodiazepines, cannabis, and cocaine throughout the 8 weeks of the experimental period, with the decrease being greater during the last four weeks of the intervention. These results suggest that the beneficial effects of exercise training occur gradually and support the view of a sequential (temporal) consolidation of exercise functions in favor of gradual disengagement from addiction [95]. Specifically, the sequence in which the mechanisms induced by exercise are unified follows the model of Internal Activation-Self-Regulation-Commitment, with the ultimate result of modifying the molecular and behavioral aspects of addiction [95].…”
Section: Discussionsupporting
confidence: 71%
“…Specifically, the sequence in which the mechanisms induced by exercise are unified follows the model of Internal Activation-Self-Regulation-Commitment, with the ultimate result of modifying the molecular and behavioral aspects of addiction [95]. Moreover, the impact of exercise on the improvement of opioid-dependent patients is more obvious when aerobic regimens of moderate intensity are applied [95], while these forms of exercise may also promote and strengthen behavioral therapeutic approaches and lead to reduced substance-consumption outcomes [94].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a notable lack of enthusiasm towards PA among individuals undergoing methadone maintenance treatment (MMT) [ 26 , 27 ]. Only 38% of individuals in MMT achieved the recommended weekly amount of PA [ 28 ].…”
Section: Introductionmentioning
confidence: 99%